ENTRAVES À EFETIVAÇÃO DA PARTICIPAÇÃO E CONTROLE SOCIAL NO BRASIL: UMA ANÁLISE A PARTIR DO CENÁRIO PÓS-DEMOCRÁTICO (Revista Paradigma, 2025)
Social control is a forceful way for citizens to participate, control and legitimize the actions of their leaders, also taking shape in a closer relationship between the State and Society. However, it is shown that today there has not been much public support for the available participatory means. The purpose of this foreshortening was to analyze the Post-Democratic period that is being experienced and how this scenario ends up generating apathy for citizens and making it impossible to fulfill their civic duty to inspect State acts through social control. In this sense, the present work tried to answer the following problem: are there any obstacles to the effectiveness of social control in Brazil, based on an analysis of the post-democratic scenario? The article started from the hypothesis that the Post-democratic scenario develops in a way that discourages and makes citizen participation and, consequently, social control unfeasible. To carry out this paper, the hypothetical-deductive research method was used and the bibliographic research technique was used. The preliminary results were that the Post-Democratic State is incompatible with the 1988 Constitution and that it hinders public participation and control, in addition to weakening civil society.